Novel triterpenoid derivatives from Eucomis bicolor Bak. (Hyacinthaceae: Hyacinthoideae). Issue 25 (8th March 2017) - Sihra, Jaspreet K.; Langat, Moses K.; Crouch, Neil R.; Nuzillard, Jean-Marc; Plainchont, Bertrand; Mulholland, Dulcie A.
Abstract : The bulbs of Eucomis bicolor (Hyacinthoideae) yielded fourteen novel compounds, including (17 S )-3-oxo-24, 25, 26, 27, 28-pentanorlanost-8-en-23, 17α-olide, whose structure was determined using the Logic for Structure Determination Program. Abstract : The bulbs of Eucomis bicolor (Hyacinthoideae) yielded fourteen novel natural compounds, including (17 S )-3-oxo-24, 25, 26, 27, 28-pentanorlanost-8-en-23, 17α-olide, whose structure was determined using the logic for structure determination program, and nine novel lanosterol glycosides. Compounds were screened against the NCI-59 cancer cell panel but showed limited activity.